IEO Report on the Evaluation of IMF Support to Jordan. (Independent Evaluation Office Reports; Independent Evaluation Office Reports, 2006)
This report evaluates the role of the IMF in supporting economic reform in Jordan during 1989-2004. The evaluation provides an opportunity to assess typical features of relations between the IMF and its borrowing members, and to put into a specific country context IEO's earlier findings on program design and the links between programs, surveillance, and technical assistance. The report highlights a number of broad lessons suggested by the IMF's experience in Jordan, as well as other lessons focusing on the IMF's future role in Jordan.